Two-Way and Multiple-Way Shape Memory Polymers for Soft Robotics: An Overview - Scalet, Giulia (Actuators, 2020)
Shape memory polymers (SMPs) are smart materials capable of changing their shapes in a predefined manner under a proper applied stimulus and have gained considerable interest in several application fields. Particularly, two-way and multiple-way SMPs offer unique opportunities to realize untethered soft robots with programmable morphology and/or properties, repeatable actuation, and advanced multi-functionalities. This review presents the recent progress of soft robots based on two-way and multiple-way thermo-responsive SMPs. All the building blocks important for the design of such robots, i.e., the base materials, manufacturing processes, working mechanisms, and modeling and simulation tools, are covered. Moreover, examples of real-world applications of soft robots and related actuators, challenges, and future directions are discussed.